2015
DOI: 10.1136/injuryprev-2014-041483
|View full text |Cite
|
Sign up to set email alerts
|

SSRI use and risk of fractures among perimenopausal women without mental disorders

Abstract: Background Selective serotonin reuptake inhibitors (SSRIs) were recently approved by the FDA to treat vasomotor symptoms associated with menopause. No prior study has directly examined whether fracture risk is increased among perimenopausal women who initiate SSRIs or among a population of women without mental disorders more generally. Methods Female patients without mental illness, aged 40-64 years, who initiated SSRIs were compared with a cohort who initiated H2 antagonists (H2As) or protonpump inhibitors (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…No relevant randomized controlled studies were found. Sixteen studies were included from the previous systematic review, and 17 studies were identified as new in the databases (Figure ) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No relevant randomized controlled studies were found. Sixteen studies were included from the previous systematic review, and 17 studies were identified as new in the databases (Figure ) …”
Section: Resultsmentioning
confidence: 99%
“…The studies we found were published between 1998 and 2016, with 11 studies since 2013 . Two studies were reported across multiple articles and each was treated as a single distinct study: Vestergaard et al and Souverein et al One study reported results from both a cohort and a nested case‐control analysis .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that there is a susceptible population of patients with impaired bone health due to pharmacological intervention for depression once thought to only include patients with pre-existing compromised bone (i.e., osteoporosis). 25 Although this topic will remain controversial, the increase in reports of interaction effects between bone health and SSRI use 14,26 is revealing a potentially larger problem not limited to osteoporosis. Further study is needed to determine if long-term SSRI treatment alters bone remodelling through other pathways such as TNF-α signalling linked to inflammation and early healing.…”
Section: Discussionmentioning
confidence: 99%
“…14 While clinical correlations between SSRI treatment and negative bone phenotypes have been established, research concerning SSRI use and bone health has only recently been extended to specific effects on bone wound healing, where it was found that fluoxetine negatively affected limb fracture healing. 15 It follows that if SSRIs can affect bone health and even bone cell activity, 1619 use may negatively affect the repair and remodelling process.…”
Section: Introductionmentioning
confidence: 99%